Competition and modernization in South Asia - Ullrich,Helen .E. (ed.) (New Delhi, 1975)
This book explores the concept that competition may serve as a key to modernization. Among an older generation of anthropologists, competition and conflict were regarded as signs that a society was in decline and in a state of disintegration. Increasingly anthropologists have come to recognize the positive attributes of competition and social conflict. This volume focuses on how competition may serve as a factor in stimulating innovation and modernization, with special reference to South Asia. The seven articles in the volume examine competition bet ween communities, between castes, bet ween families, and between co-religionists as a determining factor for modernization. Bangladesh, North India, South India and Sri Lanka are all represented in this volume espousing the view that com petition inherent in a traditional society leads a society to modernize.
Keywords: "Social change , Competitive Modernization"